1985
DOI: 10.3354/meps025305
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial growth in deep-sea sediment trap and boxcore samples

Abstract: This study was to determine whether heterotrophic bacteria associated with deep-sea particulates are adapted more to the moderate temperatures and pressures of surface waters or to the extremes of the deep sea, and how such microorganisms respond to substrate enrichment. Samples of sinking particulates, fecal pellets, and deposited sediments were collected in bottom-moored sediment traps and boxcores at station depths of 1850, 4120, and 4715 m in the North Atlantic. Homogenized seawater suspensions of samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 14 publications
2
35
0
Order By: Relevance
“…Bacterial standing stock does not necessarily correlate with metabolic activity. There is ample evidence for distinctive barophilic microbiota that rapidly degrade sinking phytoplankton (Deming 1985, Lochte & Turley 1988, but an unknown fraction of bacteria in deep-sea sediments originates in surface waters and is transported to the seafloor attached to sinking phytodetritus (Lochte & Turley 1988). Many of these appear to be dormant, either because they lack labile organic material or because of inhibitory physical conditions at great depths (Deming & Baross 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial standing stock does not necessarily correlate with metabolic activity. There is ample evidence for distinctive barophilic microbiota that rapidly degrade sinking phytoplankton (Deming 1985, Lochte & Turley 1988, but an unknown fraction of bacteria in deep-sea sediments originates in surface waters and is transported to the seafloor attached to sinking phytodetritus (Lochte & Turley 1988). Many of these appear to be dormant, either because they lack labile organic material or because of inhibitory physical conditions at great depths (Deming & Baross 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial communities in the upper layer of the ocean act as a filter, rapidly using the labile organic compounds produced by photosynthesis. During their sinking period the small size particles are subject to microbial attack (Deming 1985, Hoppe et al 1993, Poremba 1994, Turley & Mackie 1994. Conversely, the rapidly sinking larger particles or aggregates pass through this biological filter and provide the seafloor with energy-rich material.…”
Section: Introductionmentioning
confidence: 99%
“…Rowe & Deming 1985, Cahet et al 1990, Turley & Lochte 1990, Deming & Baross 1993. A critical point is the actual contribution of deep sea bacterial consortia to the coupling between pelagic and benthic activities (Deming 1985, Deming & Baross 1993, Poremba 1994, Smith et al 1994, Poremba & Hoppe 1995, Ritzrau et al 1997. Bacterial communities in the upper layer of the ocean act as a filter, rapidly using the labile organic compounds produced by photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…More speciWcally, Boetius and Lochte (1996) detected an increase in chitobiase activity 10 days after chitin addition. Investigations of Deming (1985) with deep-sea sediments amended with chitin showed that bacterial doubling time were in the order of weeks or months. Thus, bacterial growth is suYciently slow to preclude detection of signiWcant increases in cell number after 7 days of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…North Atlantic (Deming 1985); Arctic continental slope (Boetius and Lochte 1996); Arabian Sea (Christiansen and Boetius 2000)]. These studies indicated that chitin supplies induced the synthesis of speciWc enzymes and that indigenous deep-sea bacteria were able to decompose even high amounts.…”
Section: Introductionmentioning
confidence: 99%